Edukasi Laboratorium Teknik Mesin ITERA Bagi Siswa SMKN 1 Raman Utara Dalam Meningkatkan Literasi Teknologi - Fajar Paundra; Abdul Muhyi; Fajar Perdana Nurullah; Eko Pujiyulianto; Devia Gahana Cindi Alfian; Muhammad Syaukani; Kardo Rajagukguk; Dicky Januarizky Silitonga; Putra Andi Kolala; Farid Nanda Syanur; Rico Aditia Prahmana (CV. Multi Kreasi Media, 2025)
This community service activity aims to introduce the laboratory environment and facilities of the Mechanical Engineering Study Program at Institut Teknologi Sumatera (ITERA) to students of SMKN 1 Raman Utara, East Lampung. The activity was conducted in the form of a campus visit involving 62 12th-grade students from the Light Vehicle Engineering Department. The agenda included a presentation on higher education opportunities, interactive discussions, a Q&A session, and a direct tour of ITERA’s Mechanical Engineering laboratories, including the Materials Engineering, Energy Conversion, Fabrication, Manufacturing, Internal Combustion Engines, and Foundry laboratories. This activity was designed to inspire students to pursue higher education and broaden their understanding of engineering fields. The outcome showed a high level of enthusiasm among the students and successfully achieved the goal of introducing campus life and technological exposure. This initiative is expected to serve as an initial step in strengthening synergy between vocational high schools and higher education institutions.